Effectiveness of Acupressure Therapy at Points SP6 AND LI4 Against Dysmenorrhea in Adolescent Girls in College : A Pre-experimental Study - Marchatus Soleha; Vika Tri Zelharsandy; Wika Sepiwiryanti; Dewi Ciselia (Lentera Perawat, 2025)
Many teenagers experience pain during menstruation. The selection of traditional methods such as acupressure is able to reduce dysmenorrhea pain that is carried out at several acupuncture points. To overcome the problem of dysmenorrhea pain, acupressure massage therapy is carried out at SP6 and LI 4 points, which at this point can stimulate the production of endorphin hormones. Related to the production of prostaglandins in the luteal phase, acupressure is expected to be able to improve blood circulation, so that prostaglandins flow in the blood circulation and do not accumulate in the uterus and can finally reduce pain during menstruation. The purpose of this study is to find out the difference in dysmenorrhea pain before and after acupressure massage therapy at SP6 and LI 4 points. This study uses a quasi-experimental design with a one-group pretest – posttest design. The sample of this study is adolescent girls at STIKES Abdurahman Palembang as many as 20 respondents using purposive sampling The average reduction in pretest dysmenorrhea pain in the intervention group was 6.65. The mean value of the reduction in dysmenorrhea pain in the posttest of the intervention group decreased to 2.70. The results of the analysis is <0.05 (0.001), the results were significant, this proves that there is an effectiveness of acupresure at SP6 and LI 4 points against dysmenorrhea in adolescent girls.